Pengaruh kompetensi, pelatihan dan pengawasan terhadap kinerja karyawan pada PT Rubber Hock Lie Sunggal Sumatra Utara - S, Hernadhi. (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
Performance is the level of success of employees in carrying out their duties. Factors that affect employee performance are competence, training, and supervision. Competence is the ability to carry out a job that is based on skills and knowledge. Training is a process of improving employee job skills to help achieve company goals. Supervision is a process to ensure that all activities are carried out according to what has been planned. PT. Rubber Hock Lie is an international industrial company headquartered in Singapore which produces crumb rubber. The research method uses a quantitative approach, the type of research used is descriptive quantitative. The data analysis used is multiple linear regression. To test the validity and reliability of the research variable instruments, 30 respondents were taken out of the sample. The results showed that competence, training, and supervision simultaneously and partially had a positive and significant effect on employee performance with a coefficient of determination of 0.937 or 93.7%, while the remaining 6.3% was influenced by other factors. The conclusion of this research is that competency, training, and supervision simultaneously and partially have a significant effect on the performance of the employees of PT Rubber Hock Lie Sunggal.